2021
DOI: 10.1128/mcb.00517-20
|View full text |Cite
|
Sign up to set email alerts
|

Exosome-Mediated Transfer of circ_0000338 Enhances 5-Fluorouracil Resistance in Colorectal Cancer through Regulating MicroRNA 217 (miR-217) and miR-485-3p

Abstract: Background: Exosomes are microvesicles secreted by body cells for intercellular communication. Circular RNA circ_0000338 was found to present in extracellular vesicles and improve the chemo-resistance of colorectal cancer (CRC) cells. However, the role of exosomal circ_0000338 in 5-Fluorouracil (5-FU)-resistance in CRC is largely unknown. Methods: The levels of circ_0000338, microRNA (miR)-217 and miR-485-3p were detected using the qRT-PCR. The IC50 values of cells to 5-FU, cell proliferation and apoptosis wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 42 publications
3
43
0
Order By: Relevance
“…Human CRC HT-29 cells were cultured in patient-derived decellularized Another example of the tumor microenvironment association with drug resistance is extracellular vehicles (EVs), which mediate intercellular communication between cancer cells. EVs can contain small molecules such as therapeutic drugs, mRNAs, miRNAs, or even proteins, such as drug efflux transporters [49,50] . Exosome-mediated transfer of circular RNA (circ_0000338) enhanced 5-FU resistance in circular RNAtransmitted human CRC cell lines, which was achieved through its direct binding with miR-217 and miR-485-3p.…”
Section: The Tumor Microenvironment May Affect Cancer Cell Properties and Drug Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Human CRC HT-29 cells were cultured in patient-derived decellularized Another example of the tumor microenvironment association with drug resistance is extracellular vehicles (EVs), which mediate intercellular communication between cancer cells. EVs can contain small molecules such as therapeutic drugs, mRNAs, miRNAs, or even proteins, such as drug efflux transporters [49,50] . Exosome-mediated transfer of circular RNA (circ_0000338) enhanced 5-FU resistance in circular RNAtransmitted human CRC cell lines, which was achieved through its direct binding with miR-217 and miR-485-3p.…”
Section: The Tumor Microenvironment May Affect Cancer Cell Properties and Drug Sensitivitymentioning
confidence: 99%
“…Xavier et al [50] Exosome-mediated circular RNA transfer Circ_000038 was transferred to recipient cells in an exosomemediated fashion…”
Section: Colon Cancer Stem Cells/colon Cancer-initiating Cells and Drug-resistant Phenotypesmentioning
confidence: 99%
“…Previous reports have validated that the chemoresistance rate of ESCC to 5‐FU is nearly 85% ( 20 , 21 ). Various studies indicated that circRNAs played a crucial role in modulating the chemosensitivity of cancer cells to 5‐FU treatment ( 22 , 23 ). Gao et al.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy in colon cells induces significant upregulation in the expression of circ_0001313, as well as the downregulation of miR-338-3p, thus increasing CRC tumor radioresistance and suggesting a positive correlation between CRC radioresistance and circ_0001313 [ 103 ]. Other circRNAs, such as circ_0020095 [ 104 ], circ_0005963 [ 101 ], and circ_0000338 [ 105 ], have similar functions as oncogenics involved in CRC tumors.…”
Section: The Dual Role Of Circrna As Mirna Sponges In Crcmentioning
confidence: 99%